Recreation of Construction Patterns by 4-, 5- and 6-year-old Children 70 Years Ago and Today. Comparison of Test Results - Jan Amos Jelinek (Maria Curie-Skłodowska University, Lublin, Poland, 2023)
Introduction:Recreation of construction patterns is an important form of supporting students' cognitive development. Unfortunately, a lack of research makes it impossible to characterise the skills of contemporary children. Research Aim: To establish the current ability of pre-school children to reproduce constructions and to determine how these skills have changed in relation to research conducted 70 years earlier (Popiel, 1955-1957). Method: In order to compare the results of the research conducted, the tools were recreated and the method of the research conducted 70 years earlier was repeated. Seven finished constructions were presented to the children and the method of recreating them was recorded. The description included the method of construction and the correctness of the reconstructed construction. Results: The level of reproduction of the constructions is similar. However, modern children are better at recreating more difficult constructions. The small number of subjects limits the generalising power of the results of the study. Conclusions: The results of the study shed some light on children's constructional abilities. They indicate that the situation of recreating constructions can be used as a form of supporting children's mental development. The differences in the results of the studies indicate that caution should be exercised in citing research findings on the construction skills of children living many years earlier. Research is needed to explore these issues in more depth.